On the estimation of physical roughness of a marginal sea ice zone using remote sensing - Gupta, Mukesh (Hydrological Processes, 2014)
This thesis provides insight into techniques for the detection and classification of various marginal ice zone roughnesses in the southern Beaufort Sea using in situ and satellite-based microwave remote sensing. A proposed model of surface roughness shows the dependence of circular coherence, a discriminator of roughness, on the roughness and dielectrics. A relationship between ice slopes in azimuth and range direction is derived. Microwave brightness temperature of open water is significantly correlated with wave height but not with the wind speed, having the strongest correlations for the H-polarization at both 37 and 89 GHz. A modified formula for the relationship between non-dimensional form of energy and wave age at wind speeds 0−10 m/s is obtained. The brightness temperature (April−June) of sea ice at H-polarization of 89 GHz is found to decrease with increasing roughness, and is attributed to the dominant contributions from rapidly varying thermodynamic properties of snow-covered sea ice. October 2014